Perancangan Aplikasi Pemesanan Berbasis Web Menggunakan Metode Waterfall Pada UMKM Cafe Mie Ayam Rumah Mewah - Az-Zarro, Fatimah; Saprudin (CV. Shofanah Media Berkah, 2024)
MSMEs of Chicken Noodles often face difficulties in managing orders manually which leads to irregularities in order management and customer service. This ordering application is designed to make it easier for customers to order chicken noodles online, as well as to help business owners manage and monitor orders efficiently. The development process of this application uses the Waterfall approach which consists of the stages of needs analysis, system design, coding, testing, and implementation. The main features in this application include selecting a chicken noodle menu, order management, payment confirmation, and tracking order status integrated with the raw material inventory management system. This application also provides sales reports that can be used by business owners to analyze business performance periodically. The results of the application development show that the online ordering system that is built can increase efficiency in order management and speed up the service process to customers. By using the Waterfall method, application development is structured and produces products that are in accordance with the needs of MSMEs of Chicken Noodles, as well as providing convenience for customers and business owners.